Funding vs. Real Economy Shock : The Impact of the 2007-2009 Crisis on Small Firms' Credit Availability - Berg, Gunhild; Kirschenmann, Karolin (World Bank, Washington, DC, 2012)
This paper analyzes the impact of two distinct shocks stemming from the cross-border transmission of the 2007-2009 crisis on credit availability for small firms. The paper uses data from AccessBank Azerbaijan which was affected in its liquidity position during the second and third quarters of 2008 by delays in its refinancing. The Azeri real economy was hit by the global crisis from the fourth quarter of 2008 onwards with a combined decline in oil prices, exports, remittances, and domestic demand. Therefore, a pure supply side shock con be contrasted with a real economy shock that hit exactly when the bank's funding position strengthened again. The paper finds that during the funding shock (potential) borrowers are discouraged from applying for loans. However, for those applications made, the likelihood of loan approval is not affected. The real economy shock, in contrast, reduces the approval likelihood for SME loans in particular, while agro and micro loans are considerably less affected. Finally, bank relationships increase credit availability in good as well as in bad times.